ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH FACTORS IN STREET FOOD VENDORS IN PENJOMPONGAN RAYA, CENTRAL JAKARTA - Bela Zaghu, Monika; Erislan, Erislan; Sukwika, Tatan; Eddyono, Fauziah (HEARTY, 2026)
Street vendors typically sell using carts containing oil, stoves, and gas. Many street vendors work environments are frequently exposed to burn hazards, such as hot oil, hot pans, fire, electricity, and stoves. Objective: To examine occupational accidents, the causes of occupational accidents, and potential solutions to address these causes for street food vendors in Penjompongan Raya, Central Jakarta. Method: This research is qualitative, conducted through in-depth interviews. Informants in this study are street food vendors in Penjompongan Raya, Central Jakarta, with a total of 10 informants. Data collection techniques included observation and interviews, using questionnaires as data collection tools, and data analysis through data reduction, data presentation, and conclusion drawing. Research Findings: Occupational accidents were identified among street food vendors, with contributing factors including fatigue, stress, and work environment. Conclusion: There are three primary causes of occupational accidents among street food vendors: fatigue, stress, and work environment factors.